Extended O-GlcNAc on HLA class-I-bound peptides - Marino, Fabio (J Am Chem Soc, 2015)
We report unexpected mass spectrometric observations of glycosylated human leukocyte antigen (HLA) class I-bound peptides. Complemented by molecular modeling, in vitro enzymatic assays, and oxonium ion patterns, we propose that the observed O-linked glycans carrying up to five monosaccharides are extended O-GlcNAc’s rather than GalNAc-initiated O-glycans. A cytosolic O-GlcNAc modification is normally terminal and does not extend to produce a polysaccharide, but O-GlcNAc on an HLA peptide presents a special case because the loaded HLA class I complex traffics through the endoplasmic reticulum and Golgi apparatus on its way to the cell membrane, and is hence exposed to glycosyltransferases. In addition we report for the first time natural HLA class I presentation of O- and N-linked glycopeptides derived from membrane proteins. HLA class I peptides with centrally located oligosaccharides have been shown to be immunogenic and may therefore be important targets for immune-surveillance.